Preventing and Appeasing COVID-19 Vaccine Tension in Schools to Protect the Well-Being of Children and Adolescents in Québec, Canada - Santavicca, Tara; Vanier-Clément, Anabelle; Rousseau, Cécile (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: This article describes an intervention that took place in Québec, Canada, to mitigate COVID-19 vaccine tension in schools, exacerbated by the 12-17 years old vaccination campaign. Building on this initiative, it proposes guiding principles for prevention and intervention in conflict around COVID-19 vaccination in and around schools. Intervention: Three complementary tools were developed by a community program, CoVivre, in collaboration with an interdisciplinary team, to help practitioners and parents understand vaccine tensions and their impact on youth, and to suggest simple ways to prevent and intervene in vaccine related conflicts. Recommendations: A thorough research evaluation could not be performed due to the rapid crisis response; however, the tools received positive feedback by practitioners, institutions, and decision makers. Recommendations were structured around the following principles: (a) fostering transparent and nuanced health communications; (b) avoiding confrontation and refusing to escalate while strongly condemning criminal acts; (c) encouraging open dialogue; and (d) preserving relationships. Implications: Mental health consequences of public health interventions should be considered at inception to avoid collateral damages. Removing children from the heart of societal conflict and maintaining the family-school relationship is crucial to child development. It is imperative to engage interdisciplinary teams to protect youth from societal polarization, and provide an opportunity for growth and resilience. This initiative suggests that more research is needed on the impacts of encouraging an open dialogue around vaccination, and adopting an empathetic approach amongst youth towards others who may not share the same opinion.